2013
DOI: 10.1155/2013/287358
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin K2, a Naturally Occurring Menaquinone, Exerts Therapeutic Effects on Both Hormone-Dependent and Hormone-Independent Prostate Cancer Cells

Abstract: In recent years, several studies have shown that vitamin k2 (VK2) has anticancer activity in a variety of cancer cells. The antitumor effects of VK2 in prostate cancer are currently not known. In the present study, we sought to characterize the anticancer potential of VK2 in both androgen-dependent and -independent prostate cancer cells. Our investigations show that VK2 is able to suppress viability of androgen-dependent and androgen-independent prostate cancer cells via caspase-3 and -8 dependent apoptosis. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 59 publications
2
24
0
Order By: Relevance
“…Although some studies have revealed vitamin K2 exerted anticancer effect mainly by blocking the cell cycle at the G1 phase and inducing the caspase-3-mediated apoptosis, the detailed mechanism of anticancer effect of vitamin K2 remains unclear[1719]. In this study, we demonstrated vitamin K2 induced apoptosis in human bladder cancer cells via generation of reactive oxygen species (ROS) which subsequently mediated MAPK and Mitochondrial pathways.…”
Section: Introductionmentioning
confidence: 79%
“…Although some studies have revealed vitamin K2 exerted anticancer effect mainly by blocking the cell cycle at the G1 phase and inducing the caspase-3-mediated apoptosis, the detailed mechanism of anticancer effect of vitamin K2 remains unclear[1719]. In this study, we demonstrated vitamin K2 induced apoptosis in human bladder cancer cells via generation of reactive oxygen species (ROS) which subsequently mediated MAPK and Mitochondrial pathways.…”
Section: Introductionmentioning
confidence: 79%
“…The anticancer activity of VK 2 has also been demonstrated in in vivo studies of colon and prostate cancer [14,16]. A number of mechanisms underlying the anticancer properties of VK 2 have been suggested including apoptosis and cell cycle arrest [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to its established function as an antihemorrhagic agent, VK 2 has showed promise as an anticarcinogenic agent in studies involving many cancer cell types including leukemia and cancers of the liver, stomach, lung, ovary, glioblastoma, and prostate [9][10][11][12][13][14][15]. The anticancer activity of VK 2 has also been demonstrated in in vivo studies of colon and prostate cancer [14,16].…”
Section: Introductionmentioning
confidence: 99%
“…Based on our current knowledge on PM100117/18 biosynthesis, no suitable explanation to this observation can be exposed. Moreover, the naphthoquinone chromophore and its derivative compound 7 do not show in vitro cytotoxic activity (Table 1), in spite of the structural and biosynthetic connection of these products to menaquinone, whose antitumor properties have been repeatedly noted [44, 45]. Furthermore, as it was predictable from a previous report [32], removal of large portions from PM100117/18 structure, as displayed in different degrees by compounds 5, 10, 11, 12 and 13, resulted in a remarkable decrease of in vitro cytotoxicity.…”
Section: Discussionmentioning
confidence: 99%